Couve consorciada com sorgo e feijão-guandu na ocorrência de pulgões e insetos predadores - Ramos, Tatiana de Oliveira [UNESP] (2015)
The aim of this study was to evaluate the influence of planting kale (Brassica oleracea L. var. acephala DC) intercropped with sorghum (Sorghum bicolor L. Moench) and pigeon pea (Cajanus cajan) (L.) and predatory insects and factors weather on aphids Brevicoryne brassicae (L.) and Lipaphis erysimi (Kaltenbach) (Hemiptera: Aphididae). Sampling was fortnightly, with aphids sampled by visual search on upper leaves, middle and basal kale, while the presence of insect predators was observed throughout the shoot and trap traps. The aphid B. brassicae prefer the middle and basal leaves of kale single and intercropped with sorghum and basal leaves of kale with pigeon pea. Lipaphis erysimi is preferred by the middle and basal leaves of the three treatments considered. The sorghum or pigeon pea in consortium with kale reduced the population of B. brassicae and L. erysimi. The kale intercropped with sorghum or pigeon pea reduces the occurrence of B. brassicae and L. erysimi. Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) showed specificity with L. erysimi, as verified with Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera: Coccinellidae) in relation to B. brassicae. In kale intercropped sorghum to both aphid species showed to be more related to the associated predatory insects to land and meteorological factors. Kale with sorghum or pigeon pea there was a potential predation among H. convergens, Polpochila impressifrons (Dejean, 1831) (Coleoptera: Carabidae) and two species of aphid. The maximum and minimum temperatures, relative humidity and heat stroke are the physical factors that acted on the occurrence of B. brassicae and L. erysimi in kale intercropped with sorghum or pigeon pea. Kale single meteorological factors and predatory insects had to be less related to the occurrence of B. brassicae and L. erysimi